Synthesis and Characterization of a Novel Class of Lewis Acid Doped Tetraaniline - K. Basavaiah; A. V. Prasada Rao (E-Journal of Chemistry)
Boron trifluoride (BF3) doped tetraaniline with novel structure were successfully synthesized via two step method. In the first step, emeraldine base form tetraaniline was synthesized via oxidative chemical polymerization of N-phenyl-1, 4-phenylenediamine using ammonium persulphate as oxidant. In the second step involves control BF3 doping of tetraaniline using boron trifluoride etherate. As synthesized BF3 doped tetraaniline have been well characterized by UV-Visible spectroscopy, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction patterns (XRD), and scanning electron microscopy (SEM) and thermogravimetry. Thermogravimetry studies revealed that the BF3 doping improved the thermal stability of tetraaniline.